2011
DOI: 10.1007/s00405-011-1801-x
|View full text |Cite
|
Sign up to set email alerts
|

Audio-vestibular evaluation in patients with essential tremor

Abstract: The aim of this study was to investigate audio-vestibular function in patients with essential tremor. Twenty-three patients with essential tremor (46 ears) and 21 health control subjects (42 ears) were included in the present study. Patients and comparison subjects were matched for age and gender. All patient and control subjects underwent pure tone audiometric test, tympanogram, transient-evoked otoacoustic emissions and auditory brainstem response. Vestibular system was evaluated by bitermal caloric test. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The otoacoustic emission responses were abnormal in more cases than controls while the latencies of waves I, V and I–V inter-peak latencies on the brainstem auditory evoked response did not differ between patients and controls. The authors concluded that the observed sensorineural hearing loss was due to cochlear rather than the retro-cochlear pathology [20]. The difference in the age of the patients could explain the different audiometric results between the two studies.…”
Section: Resultsmentioning
confidence: 99%
“…The otoacoustic emission responses were abnormal in more cases than controls while the latencies of waves I, V and I–V inter-peak latencies on the brainstem auditory evoked response did not differ between patients and controls. The authors concluded that the observed sensorineural hearing loss was due to cochlear rather than the retro-cochlear pathology [20]. The difference in the age of the patients could explain the different audiometric results between the two studies.…”
Section: Resultsmentioning
confidence: 99%
“…Audiology testing shows high frequency sensorineural hearing loss in essential tremor patients 50. The average hearing thresholds at 250-500 Hz are higher in patients with essential tremor 51…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…ABR was not different between groups. They concluded that the abnormalities are due to the cochlea rather than an auditory brainstem pathway pathology, which is responsible for hearing loss associated with ET [42]. Yilmaz et al evaluated sensorineural hearing loss by PTA, speech recognition threshold, tympanogram, SISI, tone decay, and otoacoustic emission audiological tests in non-depressed subjects.…”
Section: Hearing Impairment and Essential Tremormentioning
confidence: 99%